A MULTIMODAL INTERACTION AND INFORMATION PRESENTATION DESIGN MODEL FOR MOBILE AUGMENTED REALITY APPLICATION - MUHAMAD NAZRI, NUR INTAN ADHANI (2016)
Mobiledevices have beenwidely used as a platform for AugmentedReality (AR) application. It is mainly employed whenever people require informational support for a task while needing to stay focus on the required task such as navigation. Effective interaction and information presentation for mobile AR environment are vital as there is a need to cater for a large amount of information into mobile AR. Due to this challenge; the capacity and the effectiveness of interaction and visual modality in mobile AR are affected. Moreover, current interactions that make use of touchscreen displays have now become the de-facto standard which limits the interaction between user and device. This research herein aims to examine the potential of multimodal concept in supporting interaction and information presentation for mobile AR application. The literature reveals that multimodal able to improve the user interaction and catering large of information. Based on existing research work, a design model for mobile AR application is proposed by integrating a multimodal concept focusing on interaction and information presentation.